Eosinophil and Eosinophil Cationic Protein Level Raising in Dermatitis Due to Food Patients - Menul Ayu Umborowati; Sawitri Sawitri; Marsoedi Hoetomo (Faculty of Medicine, Universitas Airlangga, 2015)
Background: Food allergy prevalence worldwide has been increase. Skin is secondary most often target organ in food allergy reaction. Food allergy affects 35% atopic dermatitis (AD) patients. Diagnosis of food allergy is still challenge because signs are not speciﬁc. Previous researches showed eosinophil and eosinophil cationic protein (ECP) role in food allergy reaction on gastrointestinal tract, but none on dermatitis due to food. Purpose: To evaluate eosinophil and serum ECP in dermatitis due to food. Method: This is a descriptive observational cross sectional study, with dermatitis due to food patients in Dermatovenereology Outpatient Clinic Dr. Soetomo General Hospital Surabaya as subjects. Subjects has been collected trough consecutive sampling during 3 months, then data were analysized descriptively Results: Serum ECP level of dermatitis due to food patients were above normal range in all subjects, with mean level 108.5 µg/L, lowest level 33.011 µg/L and higher level 284.849 µg/L. Mean eosinophil of dermatitis due to food patients just arise above normal limit (0.413µg/L). AD patients were 48.4% among all subjects. Mean serum ECP level of AD patients was higher (121.703 µg/L) than non-AD (96.123 µg/L). Conclusions: Eosinophil and ECP seems have role in dermatitis due to food pathogenesis. Serum ECP examination can be beneﬁts to monitor dermatitis due to food severity.Key words: dermatitis due to food, eosinophil, serum eosinophil cationic protein.